Exploring critical mathematics awareness of undergraduate voluntaries teaching mathematics - İnan, Hatice Gamze. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2021., 2021)
The purpose of this explorative case study was to explore the preservice mathematics teachers', who were teaching mathematics voluntarily to the students from low-income families, critical mathematics education (CME) awareness. Through this purpose, the focus group interview and case-based semi-structured individual interviews with the three participants, who were the cases, were conducted. The data were coded, and subthemes and themes emerged. As a result of the data analysis process, the participants' CME awareness, which may be the first step of the action praxis of Freire, were found as limited based on the components of CME awareness: (i) philosophical beliefs on the nature of mathematics, (ii) awareness of social justices, and (iii) views of teaching and learning mathematics. The three participants' CME awareness was discussed based on these three components. The two components, philosophical beliefs on the nature of mathematics and social justice awareness, were considered according to two different models, which categorize both in a hierarchical order from the lowest to the higher levels. Each case of all three was placed in the each of categories of those two models, and a covert relationship between the components of philosophical beliefs on the nature of mathematics and social justice awareness was found. Moreover, it was discussed that neither teaching voluntarily nor having classroom time with the socioeconomically disadvantaged students influence the participants' CME awareness. Similarly, the progress in the teacher education program and the learning pedagogy courses do not have an impact on CME awareness. It could be stated that preservice mathematics teachers should be supported both theoretically and practically to have CME awareness and to apply it in their classrooms.
Keywords: Volunteer workers in education.; Mathematics -- Study and teaching.